2015
DOI: 10.1016/j.ijdrr.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

A review of informal volunteerism in emergencies and disasters: Definition, opportunities and challenges

Abstract: Despite highly specialised and capable emergency management systems, ordinary citizens are usually first on the scene in an emergency or disaster, and remain long after official services have ceased. Citizens often play vital roles in helping those affected to respond and recover, and can provide invaluable assistance to official agencies. However, in most developed countries, emergency and disaster management relies largely on a workforce of professionals and, to varying degrees, volunteers affiliated with of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
379
0
21

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(407 citation statements)
references
References 51 publications
7
379
0
21
Order By: Relevance
“…Crowdsourcing, compared to citizen science, has much larger search volumes, but this is unsurprising given the commercial interest in crowdsourcing as a business model. The large peak in the term crowdsourcing coincides with large-scale efforts by citizens to search for the missing Malaysian Airplane (flight MH370); over two million people helped search for the missing aircraft by analyzing satellite images [50]. The rest of the search terms from Table 1 were then put into the Google Trends application.…”
Section: Google Trends Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Crowdsourcing, compared to citizen science, has much larger search volumes, but this is unsurprising given the commercial interest in crowdsourcing as a business model. The large peak in the term crowdsourcing coincides with large-scale efforts by citizens to search for the missing Malaysian Airplane (flight MH370); over two million people helped search for the missing aircraft by analyzing satellite images [50]. The rest of the search terms from Table 1 were then put into the Google Trends application.…”
Section: Google Trends Analysismentioning
confidence: 99%
“…search for the missing Malaysian Airplane (flight MH370); over two million people helped search for the missing aircraft by analyzing satellite images [50]. The rest of the search terms from Table 1 were then put into the Google Trends application.…”
Section: Google Trends Analysismentioning
confidence: 99%
“…Undoubtedly, among the multiple institutions and organizations related to disaster and rescue management, healthcare systems, particularly hospitals, are the main unit of providing services in disasters (3). Hospitals are faced with shortages of nursing and rescue forces in disasters (4). Also, there is the possibility of damage to the hospital and the staff during unexpected events.…”
Section: Dear Editormentioning
confidence: 99%
“…Crowdsourcing can be used for financial remuneration (Buhrmester et al, 2011) or for other, more altruistic reasons, e.g. searching for the remains of the Malaysian Airways plane that went missing in 2014 (Whittaker et al, 2015) or providing hotel and restaurant reviews on sites like TripAdvisor; other initiatives can be found in Sester et al (2014).…”
Section: Introductionmentioning
confidence: 99%